Investment property valuation today / Tim Havard. - Havard, Tim (The Chandos series on construction & facilities, 2000)
This title presents descriptions of techniques for property valuation, together with use of representative examples. The title is aimed at property professionals working in the fields of asset valuation, investment appraisal and advice.